(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article discusses the peculiarities of using hydrotherapy at different temperatures for the recovery of professional athletes. It is recognized that in modern sports medicine and rehabilitation of athletes, a whole complex of cryo and thermotherapy techniques is used - ice compresses, hydromassages, baths, heat packs, infrared lamps, paraffin wax and ice massage. In addition, contrast baths, warm and cold compresses have also proven their effectiveness in the treatment of injuries, but are now increasingly used for recovery after training. It has been proven that since the middle of the 20th century. a general opinion was formed that the application of cold ice or immersion in water reduces the temperature of the skin, subcutaneous tissue and muscles. Thermotherapy has been shown to increase tissue temperature, muscle elasticity, increase local blood flow, increase metabolite production, and reduce muscle spasm. Another area of use of this therapy was the restoration of the nervous system. According to McArdy, V. Ketch, F. Ketch, during physical exercises there is a decrease in parasympathetic activity and an increase in sympathetic activity. Which, in turn, causes the release of norepinephrine and adrenaline (sympathetic excitation), increases the contraction of the myocardium and accelerates the heart rate. In addition, there is an expansion of blood vessels in the skeletal and cardiac muscles and an increase in blood circulation. After exercise, sympathetic activity remains high, but organized and adequate recovery causes an appropriate return to the resting state. However, high-intensity, with a significant load, the volume of training without the necessary rest is a system, high sympathetic activity will be constant. Which will lead to overtraining, even in the absence of signs and symptoms. Conclusions were made that the use of therapy with the contrast effect of hot and cold water in acute injuries is based on the expected physiological effects for the recovery of the body after physical exertion. Despite the popularity of hot and cold water immersion as a recovery method for athletes, little research has been done on this topic. We find various instructions regarding the duration of the procedures in each water temperature regime, the system of their repetition, the actual temperature, the use of underwater jets, the time of adaptation to contrast therapy, etc. Therefore, the prospects of further research on this topic are quite relevant. Further studies on the ratio of the duration of hot and cold procedures are needed. Appropriate contrast treatment regimen, duration, and optimal water temperature should be verified to verify its effectiveness as a recovery method.